Information Transmission Scheme between Train and RBC Based on AES-ECC Algorithm - Junjie, Zhang; Yunshui, Zheng (Journal of physics. Conference series, 2021)
The existing information encryption scheme between the Radio Block Center (RBC) and the ground has problems such as weak keys, and the vehicle-ground information has a potential threat of being stolen. In order to ensure the safety of driving, on the basis of ensuring the correct transmission of train and ground information, research on more efficient encryption schemes has become the focus of work. In response to this trend, a hybrid encryption scheme based on AES and ECC encryption algorithms is proposed. The AES algorithm replaces the original 3DES algorithm, and the elliptic curve encryption algorithm ECC is used to encrypt the session key to improve the encryption security level. The encryption simulation, avalanche effect verification and execution efficiency test of fixed-length data are completed on Visual Stduio 2013 platform, and compared with the original encryption scheme. The results show that the scheme can meet the avalanche effect and the accuracy of data transmission, and it takes less time than the original encryption scheme, and is more suitable for two-way large-capacity information transmission between vehicles and ground.